Greenhouse Gas Mitigation in the Power Sector : Case Studies from India - World Bank (Washington, DC, 2014)
The study extends the previous work from the "India : Environmental Issues in the Power Sector" report, by applying a global overlay, that is, including greenhouse gas (GHG) emission impacts, and GHG mitigation analysis, as well as estimating the incremental costs of GHG reduction, for the two case studies, Andhra Pradesh (AP) and Bihar. The study analyzes economic, financial, and technical issues, though not necessarily environmental impacts, to then "overlay" these analyses, with a systematic process for assessing the implications of GHG business-as-usual (BAU), and reform, so as to design a new scenario, i.e., the GHG mitigation scenario. Following a revision of its scope, and methodology, the study focuses on load forecasts, based on the two case studies' projected unconstrained energy, and power demand over a twenty year planning for the BAU, and reform scenarios, broken down by consumer category: domestic, commercial, low tension/high tension industry, and agriculture. Both case studies relied heavily on a least-cost power system expansion planning software (A/SPLAN), which employs a dynamic programming algorithm. Conclusions suggest that BAU implications cannot be applied as a meaningful baseline scenario for GHG mitigation analysis in these two case studies. While emissions are lower under BAU, than under reform, the expected energy served is also substantially less: massive expected failures in electricity supply under BAU conditions would not be acceptable, thus the reform scenario was selected as a baseline reference point for GHG reduction analysis.